![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
解下列方程:(1)(2x-1)2=9(2)x2+3x-4=0(3)(x+4)2=5(x+4)(4)x2+4x=2
解下列方程:(1)(2x-1)2=9(2)x2+3x-4=0(3)(x+4)2=5(x+4)(4)x2+4x=2....
解下列方程:(1)(2x-1)2=9(2)x2+3x-4=0(3)(x+4)2=5(x+4)(4)x2+4x=2.
展开
展开全部
(1)方程开方得:2x-1=3或2x-1=-3,
解得:x1=2,x2=-1;
(2)分解因式得:(x-1)(x+4)=0,
解得:x1=1,x2=-4;
(3)方程变形得:(x+4)2-5(x+4)=0,
分解因式得:(x+4)(x+4-5)=0,
解得:x1=-4,x2=1;
(4)方程变形得:x2+4x+4=6,即(x+2)2=6,
开方得:x+2=±
,
解得:x1=-2+
,x2=-2-
.
解得:x1=2,x2=-1;
(2)分解因式得:(x-1)(x+4)=0,
解得:x1=1,x2=-4;
(3)方程变形得:(x+4)2-5(x+4)=0,
分解因式得:(x+4)(x+4-5)=0,
解得:x1=-4,x2=1;
(4)方程变形得:x2+4x+4=6,即(x+2)2=6,
开方得:x+2=±
6 |
解得:x1=-2+
6 |
6 |
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询